2022
DOI: 10.1098/rsbl.2022.0318
|View full text |Cite
|
Sign up to set email alerts
|

Migratory hoverflies orientate north during spring migration

Abstract: Migratory hoverflies are long-range migrants that, in the Northern Hemisphere, move seasonally to higher latitudes in the spring and lower latitudes in the autumn. The preferred migratory direction of hoverflies in the autumn has been the subject of radar and flight simulator studies, while spring migration has proved to be more difficult to characterize owing to a lack of ground observations. Consequently, the preferred migratory direction during spring has only been inferred from entomological radar studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Though, while it looks clear that there are cues that initiate flight of hoverflies in massive numbers, we cannot draw conclusions on the processes influencing flight direction and behaviour (but see Gao et al, 2020). Similarly, we can only postulate that they originated from the south and were moving northwards, as is usually the case in spring migration (Hawkes, Weston, et al, 2022) and considering the wind direction during the days before the findings (Appendix ).…”
Section: Discussionmentioning
confidence: 97%
“…Though, while it looks clear that there are cues that initiate flight of hoverflies in massive numbers, we cannot draw conclusions on the processes influencing flight direction and behaviour (but see Gao et al, 2020). Similarly, we can only postulate that they originated from the south and were moving northwards, as is usually the case in spring migration (Hawkes, Weston, et al, 2022) and considering the wind direction during the days before the findings (Appendix ).…”
Section: Discussionmentioning
confidence: 97%
“…This species is highly migratory, moving seasonally to higher latitudes in the spring and lower latitudes in autumn. They have been observed in June on the Isles of Scilly and in mainland Cornwall migrating northwards into the rest of Britain ( Hawkes et al , 2022 ). This species is common and widely distributed in Britain and Ireland, occurring in wide range of lowland habitats including woodland, clearings, gardens, parks and hedgerows.…”
Section: Introductionmentioning
confidence: 99%
“…The species is found across Europe, Asia, and North Africa and, as the common name suggests, is a long-distance migrant. During the springtime, the hoverfly has been documented flying at least 105 km across open ocean from the Middle East to Cyprus ( Hawkes et al , 2022 ), and has been recorded heading south in the autumn through the Alps and the Pyrenees ( Aubert et al, 1976 ; Williams et al , 1956 ). In addition, entomological radar studies above southern Britain have confirmed seasonally directed movements, revealed their huge abundance and investigated their responses to wind currents ( Gao et al , 2020 ; Wotton et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%